Compatible Solute Engineering in Plants for Abiotic Stress Tolerance - Role of Glycine Betaine - Hussain Wani, Shabir; Brajendra Singh, Naorem; Haribhushan, Athokpam; Iqbal Mir, Javed (Current genomics, 2013)
Abiotic stresses collectively are responsible for crop losses worldwide. Among these, drought and salinity are the most destructive. Different strategies have been proposed for management of these stresses. Being a complex trait, conventional breeding approaches have resulted in less success. Biotechnology has emerged as an additional and novel tool for deciphering the mechanism behind these stresses. The role of compatible solutes in abiotic stress tolerance has been studied extensively. Osmotic adjustment, at the physiological level, is an adaptive mechanism involved in drought or salinity tolerance, which permits the maintenance of turgor under conditions of water deficit, as it can counteract the effects of a rapid decline in leaf water potential. Increasing evidence from a series of in vivo and in vitro studies of the physiology, biochemistry, genetics, and molecular biology of plants suggest strongly that Glycine Betaine (GB) performs an important function in plants subjected to environmental stresses. It plays an adaptive role in mediating osmotic adjustment and protecting the sub-cellular structures in stressed plants, protection of the transcriptional and translational machineries and intervention as a molecular chaperone in the refolding of enzymes. Many important crops like rice do not accumulate glycinebetaine under stress conditions. Both the exogenous application of GB and the genetically engineered biosynthesis of GB in such crops is a promising strategy to increase stress tolerance. In this review we will discuss the importance of GB for abiotic stress tolerance in plants. Further, strategies like exogenic application and transgenic development of plants accumulating GB will be also be discussed. Work done on exogenic application and genetically engineered biosynthesis of GB will be listed and its advantages and limitations will be described.